If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3E + -13x Solving y = 3E + -13x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 3E + -13x
| (2(5-7)+6)= | | 4x^2=50-10x | | 3-75/x^2=0 | | 12.28=2g+3.66 | | 2.5+0.075*p=0.1p | | 4.72-10=8+0.67x | | 12x-9whenx=4 | | -4r-24=-51 | | 5t-2+5=2t+3t | | 4x=50-10x | | 9x-117=0 | | 9t^2-4t=0 | | 3(x-3)=3(x+1) | | 5x-10=x+20 | | 7-9=6p-6p | | 2(6+x)=14+2x | | 8n/17n | | 72=12u-3u | | 36-49x^2= | | 12-9x=-3x(x+10) | | 4k^2+6k=18 | | -9x-3=6 | | 6m=2(7m+16) | | 4a^2=1 | | (a-10).(a/10)=200 | | -10(4x+5)= | | 4/3x=36 | | h=-4.9t^2+14.7t+49 | | 9x-35=4x+14 | | 2-4cos(3x)=0 | | 3n=5+11 | | r/6=17 |